Decoding TikTok Comedy: An In-depth Analysis of KPPS Humor - Listiana Ikawati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
On social media, humour is frequently used to comment on current affairs. The purpose of this study was to identify the different kinds and purposes of humour utilized on TikTok about the KPPS phenomenon's virality. The researcher gathered 30 TikTok videos as data using the descriptive qualitative research method, and the study's two primary findings are as follows. First, the study identified five types of humour, with satire being the most prevalent (50%) among them. These categories include satire, irony, sarcasm, puns, and tall tales. Second, certain kinds of humour were employed for several reasons, including identification, differentiation, enforcement, and explanation. Additionally, a relationship between the kinds of humor and its purposes on TikTok was found. It implies that the speakers preferred specific kinds of humour for different reasons. Additionally, the speakers praised KPPS members above other culturally presumed acceptable occupations in Indonesia and denounced unethical actions by dishonest state officials or civil workers using a range of humour types and purposes. The popularity of the KPPS phenomenon and TikTok provides individuals with a safe and creative forum to voice their opinions while also raising awareness of the various social issues affecting their community.